Influence analysis of sprinkler irrigation effectiveness using ANFIS - Liang, Zhongwei; Liu, Xiaochu; Wen, Guilin; Yuan, Xuefeng (International Journal of Agricultural and Biological Engineering, 2019)
In order to improve sprinkler irrigation quality and promote actual irrigation efficiency, the influence analysis of sprinkler irrigation effectiveness (SIE) using ANFIS (Adaptive Neural Fuzzy Inference System) was implemented to balance moisture infiltration and water redistribution in soil field. Firstly, using a detailed description of governing equations proposed for sprinkler irrigation flow, the theoretical foundation and mathematical model of irrigation effectiveness can be established; Secondly, based on a complete preparation of experimental irrigation conditions, a series of calibration indexes quantifying SIE for sprinkler irrigation quality and infiltration efficiency were proposed; Then thirdly, a novel ANFIS system was designed and introduced to evaluate these key effectiveness indexes in actual working operations, so that a series of detailed influence analysis and comprehensive infiltration assessment focusing on sprinkler irrigation effectiveness could be achieved afterwards, which result to the realization of better infiltration equilibrium and higher water redistribution efficiency in actual irrigation test. Therefore, the qualification of sprinkler irrigation effectiveness was achieved, and in addition, the moisture infiltration improvement and soil moisture uniformity were facilitated also in return. Keywords: influence, analysis, sprinkler irrigation, effectiveness, ANFIS DOI: 10.25165/j.ijabe.20191205.5123 Citation: Liang Z W, Liu X C, Wen G L, Yuan X F. Influence analysis of sprinkler irrigation effectiveness using ANFIS. Int J Agric & Biol Eng, 2019; 12(5): 135–148.